79 The criminal law and unauthorised and malicious interference with automated and connected cars. (1st September 2016) - Brady, Mark; Tranter, Kieran; Rakotonirainy, Andry
Abstract : Background: Driverless cars are no longer a science fiction and is clearly looming in the transport horizon. Software and wireless networks are increasingly controlling all aspects of transport's landscape. Advances in technology have outpaced research in human factors and policy therefore serious questions must be asked about the legal protections of the integrity of these new systems to guarantee community's safety. Furthermore the research knowledge to understand and define the key safety issues that the community required to advance a policy action plan is still in its infancy. Specifically we do not know how effective are the deterrence and penalties within Australia's criminal law in respect to the unauthorised and malicious interference with in-vehicle computer systems? Method: We discuss existing and near-future scenarios where there might be unauthorised and malicious interference with in-vehicle computer systems. Examples range from a malcontent hacking a vehicle's system to cause it to crash, to a third-party installing spyware on a vehicle to gather private data about the vehicle's movements. We then articulate the range of criminal provisions, at a state and federal level that cover the unauthorised and malicious interference with in-vehicle computer systems. The lack of detailed case law (reflecting a very low level of prosecutions) suggests that overarching difficulties might lie with the forensics of investigation and known problems with the policing of cybercrimes. Results: We show how Australian criminal law could cover future scenarios. We demonstrate a lack of case law suggesting that overarching difficulties might lie with the forensics of investigation and known problems with the policing of cybercrimes. Conclusion: This paper will help policy makers to build up a clear understanding of the adequacies of Australian state and federal criminal law successfully support transitioning into future of cooperative and autonomous transport systems.